O Indivíduo sobre três perspectivas diferentes, e nos livros didáticos do ensino fundamental II - Machado, Diogo Lucas Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The individual is on the axiomatic basis for many sciences and schools of thought, especially when dealing with human action, and defining it always brings a debate. This debate will be in this research through the individual for the Marxist school, anarchist and Austrian school, their different views and what they imply for knowledge and approach. The result of this debate is a collectivist or individualistic view, and which of these visions interests the state and what will it use in the curricula? The school is very important in the life of the individual, who stays years of his life submissive to curricula elaborated by governments, and the geography as discipline also treats the individual with subjects that involve the human action, and with the growth of the critical geography in the last decades, how the individual will be uttered, debated and analyzed of the critical geography and in the didactic books produced by it? In this research we will analyze and discuss about the individual in the textbook of elementary education II, and where is the I in geography?

O indivíduo está na base axiomática para muitas ciências e escolas de pensamento, principalmente quando tratam de ação humana, e defini-lo traz sempre um debate. Esse debate vai estar nessa pesquisa através do indivíduo para a escola marxista, anarquista e escola austríaca, suas diferentes visões e no que elas implicam para o conhecimento e abordagem. O resultado desse debate é uma visão coletivista ou individualista, e qual dessas visões interessa ao Estado e que ele vai utilizar nos currículos? A escola é muito importante na vida do indivíduo, que fica anos de sua vida submisso a currículos elaborados por governos, e a geografia enquanto disciplina também trata do indivíduo com temas que envolvem a ação humana, e com o crescimento da geografia crítica nas últimas décadas, como o indivíduo vai ser proferido, debatido e analisado nos livros didáticos por ela produzida?
Keywords: Geografia; Escola austríaca de economistas; Escola marxista de sociologia; Anarquismo e anarquistas